Home blood‐pressure monitoring in a hypertensive pregnant population. (22nd February 2018) - Perry, H.; Sheehan, E.; Thilaganathan, B.; Khalil, A.
ABSTRACT: Objective: The majority of patients with chronic or gestational hypertension do not develop pre‐eclampsia. Home blood‐pressure monitoring (HBPM) has the potential to offer a more accurate and acceptable means of monitoring hypertensive patients during pregnancy compared with traditional pathways of frequent outpatient monitoring. The aim of this study was to determine whether HBPM reduces visits to antenatal services and is safe in pregnancy. Methods: This was a case–control study of 166 hypertensive pregnant women, which took place at St George's Hospital, University of London. Inclusion criteria were: chronic hypertension, gestational hypertension or high risk of developing pre‐eclampsia, no significant proteinuria (≤ 1+ proteinuria on dipstick testing) and normal biochemical and hematological markers. Exclusion criteria were maternal age < 16 years, systolic blood pressure > 155 mmHg or diastolic blood pressure > 100 mmHg, significant proteinuria (≥ 2+ proteinuria on dipstick testing or protein/creatinine ratio > 30 mg/mmol), evidence of small‐for‐gestational age (estimated fetal weight < 10 th centile), signs of severe pre‐eclampsia, significant mental health concerns or insufficient understanding of the English language. Pregnant women in the HBPM group were taught how to measure and record their blood pressure using a validated machine at home and attended every 1–2 weeks for assessment depending on clinical need. The control group was managed as per the local protocol prior to the implementation of HBPM. The two groups were compared with respect to number of visits to antenatal services and outcome. Results: There were 108 women in the HBPM group and 58 in the control group. There was no difference in maternal age, parity, body mass index, ethnicity or smoking status between the groups, but there were more women with chronic hypertension in the HBPM group compared with the control group (49.1% vs 25.9%, P  = 0.004). The HBPM group had significantly fewer outpatient attendances per patient (6.5 vs 8.0, P  = 0.003) and this difference persisted when taking into account differences in duration of monitoring (0.8 vs 1.6 attendances per week, P  < 0.001). There was no difference in the incidence of adverse maternal, fetal or neonatal outcome between the two groups. Conclusion: HBPM in hypertensive pregnancies has the potential to reduce the number of hospital visits required by patients without compromising maternal and pregnancy outcomes. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations.